Mapping Monthly Average Global Solar Radiation over Iraq Using GIS and Heliosat Model - Z. Ali, Hussain; AL-Salihi, Ali. M.; AL-Abodee, Ahmed. K. (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2016)
The mapping of global solar radiation is important in designing of solar energy system and renewable energy applications, also the global solar radiation estimation and mapping will facilitate engineers and architect purposes and applications. In present paper measured and estimated global solar radiation data was employed. The estimation of global radiation data can give results with acceptable accuracy to establish solar maps of monthly radiation using Geographic Information Systems (GIS) software. Simple Kriging interpolation was used to derive radiation maps over Iraq. Â Different models were employed, namely Spherical, Circular, and Gaussian. Solar radiation data for the years 1985,1990,1995,2000 and 2005 were used for the production of solar radiation maps over Iraq. On average, Iraq receives (5000) kWh/m2 of global solar radiation in year 2005. The highest global solar radiation is estimated at 6790kWh/m2 in September while the lowest is 1660 kWh/m2in December. Cross validation was used to find the best model by comparing the error criteria, namely MPE, RMS, MSPE, RMSS, and ASE. It was found the Spherical model gives best results according to the cross validation error criteria. Mapping Monthly Average Global Solar Radiation over Iraq Using GIS and Heliosat Model